ANALISIS PEMANFAATAN HUTAN WAKAF DALAM PEMBERDAYAAN MASYARAKAT DESA CIBUNIAN KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Suhendar, Cecep; Pujiharto, Yaya RC; Misno (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2024)
The aim of this research is to evaluate the use of waqf forests in an effort to empower the community in Cibunian Village. Pamijahan District, Bogor Regency. Qualitative Research in the Postgraduate Sharia Economics Master's Study Program at the Sahid Bogor Islamic Institute. November 2023. This research aims to understand and evaluate the use of waqf forests in an effort to empower the community of Cibunian Village, located in Pamijahan District, Bogor Regency, as well as to examine and determine the obstacles and challenges faced by the community in Utilizing Waqf Forests. This research uses a descriptive qualitative approach method used in this research. Data collection was carried out through observation, interviews and documentation studies. Data analysis adopts the interactive approach of the Miles and Huberman Model, which involves the stages of data collection, data presentation, and drawing conclusions. Triangulation is carried out by utilizing various data sources and methods, namely source triangulation and method triangulation. From the information obtained and the data analysis that has been carried out, as well as the discussion presented in the previous chapter, conclusions can be drawn regarding the Utilization of Waqf Forests in Community Empowerment Efforts in Cibunian Village, Pamijahan, Bogor Regency, as follows: Environmental sustainability, waqf forests have provided good potential for efforts to prevent soil erosion, and income for waqf forest management groups, although not yet optimal in Cibunian Village, Pamijahan District, Bogor Regency. Empowerment and utilization of waqf forests has contributed to poverty alleviation and provided economic potential for communities managing or waqf forest groups, one of which is empowering Small and Medium Enterprises (UKM) and also planting fruit trees whose results are managed by groups in the Cibunian Village area, part of the District Pamijahan, which is located in Bogor Regency Productive Waqf Forests have not had a significant impact on improving community welfare because there are still limitations in revenue. Waqf forest management still focuses on physical Islamic religious tertiary institutions are expected to produce graduates who are qualified and have an entrepreneurial spirit who are able to create jobs. Likewise, an Islamic educational institution, in this case the Private Islamic Religious College (PTKIS), especially the Bogor Sahid Islamic Institute (INAIS), must continue to strive to improve quality in an effort to maintain its existence and survive amidst the very tight competition in the world of education today. . To achieve these ideal conditions, higher education institutions in general and in this case INAIS must clearly have a vision and mission that are in line with today's, tomorrow's and future needs. The purpose of this study is to analyze the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University. The type of research used is qualitative research with a descriptive analytical case study approach and library research. The results in the study show that the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University has not been fully achieved because there are obstacles faced by the Sahid Islamic Institute, one of which is because there are many graduate or alumni professions who are not entrepreneurs so that a strategy is needed, namely to improve education. and teaching, research and community service as well as supported by infrastructure that supports the achievement of entrepreneurial competence.